Brave like me - Kerley, Barbara (National Geographic, 2016)
"When someone is serving our country, far from home, everyone in their family has to be brave. Including -- and sometimes especially -- the kids. This book speaks to all kids in this situation in telling the story of a boy and a girl with parents away on duty. It captures the children's worries, fears, trials, and triumphs while waiting for their parents to return from service. Although the narrative tells one universal tale, the photographs depict multiple perspectives so that every reader has someone they can relate to. In the end, each child finds the strength and patience to endure the wait, showing admirable bravery and inspiring us all. An afterword looks further at the meaning of bravery and offers resources for helping kids deal with transition, deployment, and separation. "--